Gratitude, gratitude intervention and well-being in Malaysia - Noor, Noraini M.; Abdul Rahman, Nur Diana; Mohamad Zahari, Muhammad Idlan Afiq (Srinakharinwirot University-Behavioral Science Research Institute, 2018)
Gratitude has generally been neglected by psychologists due to the emphasis on the medical model. A dearth of research on gratitude in Malaysia was the main impetus for these studies. Study 1 compared the gratitude scores Malaysian Malays against the US, UK, China and Japan, along an individualist-collective continuum, and results showed Malays had lower gratitude scores than the others, except for the Japanese. To increase their gratitude scores, Study 2 carried out an intervention using ‘the three good things’ exercise on 59 students over a period of 14 days. The intervention increased gratitude and life satisfaction as well as reduced distress. Furthermore, a hierarchical regression examining the effect of gratitude on well-being controlling for measures of affect and religiosity at Time 1, showed that Time-2 gratitude was only predictive of Time-2 distress. The results are discussed with respect to the collectivist culture of the Malays where negative aspects of the self are valued as a form of self-criticism to help one to constantly improve oneself. Two main implications are noted: that there are cross-cultural differences in the way gratitude is understood and expressed in the Malay culture, and that engaging in positive activity may sometimes be counterproductive to well-being.